1464. Real-World (RW) Utilization Pattern of Letermovir in Adult Cytomegalovirus Seropositive Allogeneic Hematopoietic Stem Cell Transplant (HCT) Recipients: A Multicenter Retrospective Cohort Study from the European Society for Blood and Marrow Transplantation (EBMT) Registry. (15th December 2022) - Styczynski, Jan; Tridello, Gloria; Knelange, Nina; Wendel, Lotus; Xhaard, Alienor; Cutini, Ilaria; Chiusolo, Patrizia; Franke, Georg-Nikolaus; Kraus, Sabina; Raval, Amit D; Merchant, Sanjay; de la Camara, Rafael
Abstract: Background: Letermovir (LET) prophylaxis in CMV seropositive (R+) allogeneic (allo) HCT recipients was approved in 2017 based on a Phase 3 randomized clinical trial (RCT) demonstrating lower rates of CMV infection, disease, and all-cause mortality among LET treated participants. While RCTs demonstrate causal effects between treatments and outcomes, RW data answer practical aspects of utilization such as time to initiation of LET and duration of use. The objective of this study was to assess LET RW utilization pattern in adult CMV R+ recipients of allo-HCT in a large cohort of multiple centers in Europe participating in the EBMT registry. Methods: A retrospective observational cohort design was used to examine the RW utilization patterns of LET among CMV R+ of an allo-HCT in France, Germany & Italy. Inclusion criteria were CMV R+ recipients > 18 years who received LET for any reason between Jan 1 2018- Dec 31, 2020 and had data available for at least until 100 days post-HCT. Results: In this interim analysis, 138 allo-HCT recipients (52% male) with median age 55 years (range 19-72) received LET as primary prophylaxis. Donor/recipient CMV serostatus was D+/R+ 64% D-/R+ 36%. Donor type was 65% unrelated, 20% mismatched relative, 15% sibling. Standard conditioning was used in 56% and reduced-intensity in 44%. Peripheral blood stem cells were the source in 89%. T-cell depletion was performed in 48%. All centers followed WHO standardization guidelines for CMV viral load assay by PCR. Viral load was determined at time of LET initiation in 86% patients. Oral (PO) only LET formulation was used in 98% of patients (median 2 days post HCT; LET was initiated prior to HCT in 3% of the recipients). Centers indicated that intravenous (IV) formulation was administered only if patients could not tolerate PO. The median duration of PO use was 98 days. LET dose was 240 mg (86%) mostly in patients receiving cyclosporine, 480 mg (9%) or sequentially 240/480 mg (5%). Conclusion: Some differences were observed in this interim RW LET analysis compared to the phase 3 RCT. Notably, patients began LET at a median of D+2 post HCT (compared to D+9 in the trial), and 98% received only PO LET (as compared to 26.5% receiving IV LET in the trial). Further studies are needed to determine drivers of LET utilization in RW settings. Disclosures: Jan Styczynski, MD, PhD, MSD: Honoraria Amit D. Raval, PhD, Merck and Co., Inc.: Employee of Merck|Merck and Co., Inc.: Stocks/Bonds Sanjay Merchant, PhD, Merck & Co., Inc.: Stocks/Bonds Rafael de la Camara, MD, MSD: Honoraria.